Bring your paper into the 'Fast Lane' of the editorial process and increase your changes for final acceptance in Micron, The International Research and Review Journal for Microscopy. (July 2015) - Braet, Filip; Egerton, Ray; Cox, Guy
Abstract: In the past few years Micron has revised the scope of the journal, bringing it back to its original core values when it was founded in 1969. Micron's aim is to be the leading international microscopy and microanalysis journal, covering the latest advances in the fields of biological and physical science. In order to achieve this, the editorial team carefully revised the guidelines to authors in 2011. As a team we now find it timely to report on the outcomes of this policy change.